KORELASI DUKUNGAN SOSIAL DENGAN KESEHATAN JIWA SANTRI PUTRA DI PONDOK PESANTREN LUMAJANG - Priasmoro, Dian Pitaloka (Universitas Tribhuwana Tunggadewi, 2020)
Indonesia have various form of schools both regular and pesantren-based. The student of pesantren or Islamic Boarding School lack of time to be able to gather with family and home environment and cause problems in the mental health of the students. This study aims to analyze the relationship of social support with the mental health of students in Islamic Boarding School conducted in May 2020. The design used in this study is observasional (cross sectional), the population is all male students in F block totaling 50 people, the sample is part students totally 42 people. The sampling technique used was simple random sampling, the instruments used were social support questionnaire and Mental Health Inventory. Data collected by sharing the google form link, then the data was coding, editing, tabulating and analyzed univariate by percentage and bivariate by the Sommers'd test. The results showed that social support of large students in the medium category was 30 people (71.4%), mental health of almost all students had mental health with a prosperous enough life of 36 people (85.7%), and there was a fairly strong relationship between social support with mental health with a value of co-eficient correlation 0.434 and p-value 0.007 which is possible due to various factors such as the age of the student, length of stay in boarding school, support from friends or parents. Based on the results of the study it is suggested that teacher at Islamic boarding school must conduct communication activities more often so that students can talk about problems they are facing and not feel alone.